2015
DOI: 10.1137/130948136
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Data-Driven Stochastic Method for Elliptic PDEs with Random Coefficients

Abstract: Abstract. In this paper, we propose a multiscale data-driven stochastic method (MsDSM) to study stochastic partial differential equations (SPDEs) in the multiquery setting. This method combines the advantages of the recently developed multiscale model reduction method [M. L. Ci, T. Y. Hou, and Z. Shi, ESAIM Math. Model. Numer. Anal., 48 (2014), pp. 449-474] and the datadriven stochastic method (DSM) [M. L. Cheng et al., SIAM/ASA J. Uncertain. Quantif., 1 (2013), pp. 452-493]. Our method consists of offline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…For stochastic problems, one can use multiscale finite element framework with Monte Carlo techniques or separation of variables. A promising approach for solving multiscale stochastic problems is to use data driven stochastic method concepts as shown in [69].…”
Section: Discussionmentioning
confidence: 99%
“…For stochastic problems, one can use multiscale finite element framework with Monte Carlo techniques or separation of variables. A promising approach for solving multiscale stochastic problems is to use data driven stochastic method concepts as shown in [69].…”
Section: Discussionmentioning
confidence: 99%
“…We found that many high-dimensional SPDE and RPDE problems have certain low-dimensional structures, in the sense of Karhunen-Loève expansion (KLE) [20,23], which suggest the existence of reduced-order models and better formulations for efficient numerical methods. Motivated by this observation, we have made progress in developing data-driven stochastic method (DSM) to solving high-dimensional RPDE problems [10,39,38,19].…”
Section: The Data-driven Stochastic Methodsmentioning
confidence: 99%
“…We also make some progress in developing numerical methods for multiscale PDEs with random coefficients by exploring the low-dimensional structure of the solutions and constructing problemdependent basis functions to solve these RPDEs. In [10,38,19], we proposed the data-driven stochastic methods to solve partial differential equations with high-dimensional random input and/or multiscale coefficients. We found that the data-driven stochastic basis functions can be used to solve the RPDEs with many different force functions.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], Peterseim used the numerical upscaling techniques to compute eigenvalues for a class of linear second-order selfadjoint elliptic partial differential operators. Using similar methodology to construct lowdimensional generalized finite element spaces is pioneered by the generalized finite element method (GFEM) [1] and the multiscale finite element method (MsFEM) [11,14,15], and is pervasive in the recent developments in the numerical methods for multiscale problems and elliptic PDEs with random coefficients, see [8,34] and references therein.…”
Section: )mentioning
confidence: 99%